Dengue Virus-2 Infection Affects Fecundity and Elicits Specific Transcriptional Changes in the Ovaries of Aedes aegypti Mosquitoes - Feitosa-Suntheimer, Fabiana; Zhu, Zheng; Mameli, Enzo; Dayama, Gargi; Gold, Alexander S.; Broos-Caldwell, Aditi; Troupin, Andrea; Rippee-Brooks, Meagan; Corley, Ronald B.; Lau, Nelson C.; Colpitts, Tonya M.; Londoño-Renteria, Berlin (Frontiers in Microbiology, 2022)
Dengue fever (DF), caused by dengue virus (DENV), is the most burdensome arboviral disease in the world, with an estimated 400 million infections each year. The Aedes aegypti mosquito is the main vector of DENV, and transmits several other human pathogens including Zika, yellow fever and chikungunya viruses. Previous studies have shown that pathogen infection of mosquitoes can alter reproductive fitness, revealing specific vector-pathogen interactions that are key determinants of vector competence. However, only a handful of studies have examined the effect of DENV infection in Ae. aegypti, showing a reduction in lifespan and fecundity over multiple blood meals. To provide a more comprehensive analysis of the impact of DENV infection on egg laying and fecundity, we assessed egg laying timing in DENV-2 blood fed (infected group) compared to mock blood fed mosquitoes (control group). We confirmed a significant decrease in fecundity during the first gonotrophic cycle. To further investigate this phenotype and the underlying DENV-2 infection-dependent changes in gene expression, we conducted a transcriptomic analysis for differentially expressed genes in the ovaries of Ae. aegypti infected with DENV-2 versus mock infected mosquitoes. This analysis revealed several DENV-2 regulated genes; among them, we identified a group of 12 metabolic genes that we validated by RT-qPCR. Interestingly, two genes found to be upregulated in DENV-infected mosquito ovaries exhibited an antiviral role to DENV-2 in an Aedes cell line. Altogether, this work offers useful insights into the virus-vector interface, highlighting the importance of gene expression changes in the mosquito’s ovary during DENV-2 infection in the first gonadotrophic cycle, triggering antiviral responses that may possibly interfere with mosquito reproduction. This information is extremally relevant for further investigation of Ae. aegypti’s ability to tolerate viruses, since virally infected mosquitoes in nature constitute a powerful source of supporting viruses during intra-epidemic periods causing a huge burden in the public health system.